Prediction of Heart Disease Using Data Mining Technique - Joshi, Ranjana; Sethi, Shilpa (International Journal of Computer Sciences and Engineering, 2018)
In the past few decades, heart diseases had been found as leading cause of death across the world. But at the same time, it is also discovered as most preventable and controllable disease. Further, it is identified that its early and timely diagnosis helps in controlling its growth and reducing treatment cost remarkably. So it become essential to discover accurate and reasonable tools capable of extracting high risk data for timely diagnosis of such a critical disease The proposed work aims to identify vital parameters leading to heart diseases and develop a model based on data mining techniques.